Molecular and cytogenetic evaluation of y chromosome in spontaneous abortion cases - (:unkn) unknown (Halic Universitesi Fen-Edebiyat Fakultesi, 2010)
Infertility is defined as not being able to get pregnant despite having frequent, unprotected sex for at least a year. Several conditions contribute to infertility and 50% is considered to be caused by a male-related factor. Spontaneous abortion (SAB) is noninduced embryonic or fetal death or passage of products of conception before the 20th week of pregnancy and is the most common complication of early pregnancy. SAB can occur by teratogenic factors, advanced maternal age, genetic factors such as Y chromosome microdeletions and chromosomal anomalies. In order to investigate the etiology of recurrent pregnancy loss (RPL) and to develop an appropriate therapeutic strategy, it is necessary to ascertain the molecular and cytogenetic basis of these defects. In this study, we aimed to reveal the relations between male infertility, Y chromosome microdeletions and SAB. Thirty couples with a spontaneous abortion history and thirty fertile men were recruited to the study. All the women were 46, XX and men were 46, XY. We couldn't detect any Y chromosome microdeletion that could be the reason for SAB. In order to evaluate effect of chromosome anomalies and Y chromosome microdeletions on SAB, further studies with increased number of cases and controls need to be carried on.
Keywords: Infertility; Spontaneous abortion; Y chromosome microdeletions